2017
DOI: 10.3389/fncel.2017.00219
|View full text |Cite
|
Sign up to set email alerts
|

RgIA4 Potently Blocks Mouse α9α10 nAChRs and Provides Long Lasting Protection against Oxaliplatin-Induced Cold Allodynia

Abstract: Transcripts for α9 and α10 nicotinic acetylcholine receptor (nAChR) subunits are found in diverse tissues. The function of α9α10 nAChRs is best known in mechanosensory cochlear hair cells, but elsewhere their roles are less well-understood. α9α10 nAChRs have been implicated as analgesic targets and α-conotoxins that block α9α10 nAChRs produce analgesia. However, some of these peptides show large potency differences between species. Additionally several studies have indicated that these conotoxins may also acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 81 publications
4
69
1
Order By: Relevance
“…One of these analogs, RgIA4, showed a~300-fold increase in potency and, critically, was > 1000-fold more potent on a9a10 nAChRs than a7 nAChRs. As previously discussed, RgIA4 has been shown to be an effective analgesic and prophylactic in the oxaliplatin model of neuropathic pain [112,143]. Additional conopeptides have also been recently discovered that selectively target a9-containing nAChRs [160,161].…”
Section: Potential Roles Of A9-containing Nachrs In Neuropathic Pain mentioning
confidence: 92%
See 1 more Smart Citation
“…One of these analogs, RgIA4, showed a~300-fold increase in potency and, critically, was > 1000-fold more potent on a9a10 nAChRs than a7 nAChRs. As previously discussed, RgIA4 has been shown to be an effective analgesic and prophylactic in the oxaliplatin model of neuropathic pain [112,143]. Additional conopeptides have also been recently discovered that selectively target a9-containing nAChRs [160,161].…”
Section: Potential Roles Of A9-containing Nachrs In Neuropathic Pain mentioning
confidence: 92%
“…Functionally, a9* nAChRs have been shown to modulate the release of IL-1b from human monocyte-derived U937 cells as well as from mouse peripheral blood mononuclear leukocytes [83, 135,136]. It is important to point out that in these studies nicotine functioned as an agonist in contrast to the antagonist action observed for oocyte-and hair cell-expressed a9* nAChRs [6, 112,123]. Furthermore, unlike oocyteand hair cell-expressed a9* nAChRs, those found in U937 cells and leukocytes do not function as canonical ligand-gated ion channels; application of agonists that activate oocyte-or hair cell-expressed a9-containing nAChRs do not evoke ion currents in tested immune cells.…”
Section: Potential Roles Of A9-containing Nachrs In Neuropathic Pain mentioning
confidence: 99%
“…Neither paclitaxel nor RgIA4 affected heat allodynia, as measured by the Hargreaves test, nor the weight gain of the animals over the course of the experiment (Figure 4). The dosages of 80 and 16 µg/kg were chosen based on previously characterized regimens that effectively produced relief in neuropathic pain models in mice and rats [24,25]. These dosages have been previously reported to produce no adverse effects in motor coordination nor CNS function based on rotarod and Irwin tests [25].…”
Section: Rgia4 Accelerates Recovery From Paclitaxel-induced Allodyniamentioning
confidence: 99%
“…RgIA4 has been previously shown to prevent the induction of CIPN pain by the platinum-based chemotherapeutic, oxaliplatin [24,25]. Since chemotherapeutic agents work by different mechanisms of action to inhibit tumor growth, we wished to assess the activity of RgIA4 in taxane-induced neuropathic pain [39].…”
Section: α9α10 Nachrs As a Target For Pain Treatmentmentioning
confidence: 99%
See 1 more Smart Citation